PcrV Immunization Enhances Survival of Burned Pseudomonas aeruginosa-Infected Mice - Holder, Ian Alan (American Society for Microbiology, 2001)
Burned Pseudomonas aeruginosa-infected mice immunized against PcrV, a type III virulence system translocating protein, showed significantly enhanced survival compared to controls. Survival was non-O serotype specific and correlated with a reduced systemic microbial load. Infection with a high-level toxin A-producing strain required supplemental antitoxin treatment to enhance survival.